PERAN GANDA ISTRI DALAM MENSEJAHTERAKAN KELUARGA DALAM PERSPEKTIF FEMINISME AMINA WADUD - nijar, Ahmat (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study examines the dual role of wives in family welfare. Many wives are found who play a dual role in building a family in the city of Padangsidimpuan, so it is interesting to be investigated in depth. This research is included in juridical-normative legal research. The data collection method used was interviews with women who played a dual role in building family welfare. The result of this study is that the dual role of wives in building family welfare because the husband's income is not sufficient for household needs, the husband wanders, and cannot work because of illness. Ideally, all actions taken by the wife to meet the needs of the family. Meanwhile, Article 80 Paragraph 4 Letter (c) of the IHL emphasizes that the husband is the family, so that it becomes a central position in determining the progress or decline of the household. In the perspective of Islamic Family Law, balance and cooperation between husband and wife in all aspects of family life. This includes the division of tasks, decision-making, and conflict resolution, with the aim of creating a harmonious and prosperous family environment. Meanwhile, according to Amina Wadud's gender theory, the wife has a dual role in family welfare, namely first, as a life partner, the wife is responsible for supporting the husband and maintaining the integrity of the family. Secondly, as an individual who has her own rights, the wife also has the responsibility to ensure that her needs and aspirations are also met.